Physiological and performance responses to a 6-day taper in middle-distance runners: influence of training frequency - Mujika, I.; Goya, A.; Ruiz, E.; Grijalba, A.; Santisteban, J.; Padilla, S. (International Journal of Sports Medicine, 2002)
The purpose of this investigation was to examine the influence of training frequency on performance and some physiological responses during a 6-day taper. After 18 weeks of training, 9 male middle-distance runners were assigned to a high frequency taper (HFT, n = 5) or a moderate frequency taper (MFT, n = 4), consisting of training daily or resting every third day of the taper. Taper consisted of an 80 % nonlinear progressive reduction in high intensity interval training. Blood samples were obtained, and 800m performance and peak blood lactate ([La] peak ) measured before and after taper. Performance improved significantly after HFT (121.8 +/- 4.7 vs 124.2 +/- 4.9 s, p < 0.05), but not after MFT (126.6 +/- 2.8 vs 127.1 +/- 2.1 s). Neutrophils (2.89 +/- 0.68 vs 2.56 +/- 0.61 10 (3) x mm (-3)), granulocytes (3.08 +/- 0.70 vs 2.77 +/- 0.66 10 (3) x mm (-3)), haptoglobin (79.7 +/- 47.9 vs 60.7 +/- 33.6 mg x dl (-1)), total testosterone (7.39 +/- 1.67 vs 5.52 +/- 0.88 micro g x l (-1)) and [La] peak (15.5 +/- 1.5 vs 14.4 +/- 2.0 mmol x l (-1)) significantly increased with taper. [La] peak correlated with performance time before taper (r = -0.76, p < 0.05), and change in [La] peak with change in serum cortisol (r = -0.75, p < 0.05) and total testosterone:cortisol ratio (r = 0.82, p < 0.01). In conclusion, training daily during a 6-day taper brought about significant performance gains, whereas resting every third day did not. High [La] peak and a hormonal milieu propitious to anabolic processes seemed to be necessary for optimum performance.